Interspace for empathy: engaging with work-related uncertainty through artistic intervention in management education. Issue 3 (4th July 2022) - Lafaire, Ana Paula; Kuismin, Ari; Moisander, Johanna; Grünbaum, Leni
ABSTRACT: How can artistic intervention facilitate empathic engagement with work-related uncertainty in postgraduate management education? To examine this, we theorize artistic intervention as creating an interspace of temporarily suspended organizational norms through which empathy as relational knowing can emerge between participants. Drawing on an ethnographic study entitled Becoming in Academia, a nine-month artistic intervention conducted by a group of doctoral students in a Nordic business school (NBS), this paper highlights how an interspace for empathic engagement with work-related uncertainty was created by the participants through three intervention activities: aligning oneself to the other, narrating a collective validation, and acknowledging the agency of the other . In contributing to arts-based management education research, the paper theorizes and empirically elaborates on empathic knowing as emerging from activities of artistic intervention, opening an interspace, and providing new insight into arts-based methods as means for engaging with uncertainty within management education.